A variational principle for three-dimensional water waves over Beltrami flows. (July 2019) - Lokharu, E.; Wahlén, E.
Abstract: We consider steady three-dimensional gravity–capillary water waves with vorticity propagating on water of finite depth. We prove a variational principle for doubly periodic waves with relative velocities given by Beltrami vector fields, under general assumptions on the wave profile.